El crédito productivo y su incidencia en la producción agrícola del Ecuador (Estudios) - Chagerben, Lenin (2019)
The agricultural sector is very relevant in the Ecuadorian economy, due to its great contribution as a source of employment as well as to the national GDP. Thus, public policies and strategies are focused on the agricultural production sustained growth. An instrument of these policies has been the granting of productive credits – it is important to emphasize that the private sector registers a significant contribution regarding these credits, being this, greater than the one registered in the public sector. The objective of this research was to explore the evolution of agricultural productive credit and its impact on agricultural production, delimited by planning areas, period 2005-2018. The hypothesis was: the increasing in the level of granted credits, both public and private, contributes to agricultural production growth; which was not accepted according to the analyzed evidence.